Influence of hot corrosion on pulsed current gas tungsten arc weldment of aerospace-grade 80A alloy exposed to high temperature aggressive environment. (May 2022) - Subramani, P.; Arivazhagan, N.; Selvaraj, Senthil Kumaran; Mancin, Simone; Manikandan, M.
Highlights: The performance of alloy 80A weldment in a high-temperature aggressive environment was studied. The effect of hot corrosion on different welding techniques (GTAW and PCGTAW) and filler wires (ERNiCrMo-3 and ERNiCr-3) were studied. Influence of PCGTAW technique in protecting the surface of the welded substrate from an aggressive environment.IV) The mechanism of the formation of corrosive and protective oxides and its effect on the corrosion behaviour of welded substrates were studied. Abstract: One of the significant issues that shorten the life of components used in high-temperature applications is hot corrosion. The current study compares the performance of welded aerospace-grade 80A fabricated through continuous and pulsed gas tungsten arc welding techniques. Weld coupons are produced using two different filler wires (ERNiCrMo-3 (Mo-3) and ERNiCr-3 (Cr-3)). Welded substrates are subjected to 50 cycles of air oxidation and Na2 SO4  + 60%V2 O5 molten salt environmental conditions at 900 °C. Corrosion products were analysed through scanning electron microscope/energy dispersive spectroscopy and X-ray diffraction analyses. Thermogravimetric analysis revealed that all welded substrates trailed the parabolic rate of law kinetics. In the molten salt (MS) environment, gas tungsten arc welded (GTAW) Mo-3 substrate showed more weight gain. In contrast, a minor weight gain was observed in the pulsed current gas tungsten arc welded (PCGTAW) Cr-3 substrate. It indicates that accelerated corrosion kinetics was observed in the molten salt environmental condition that showed more weight gain than air oxidation. amongst the weldments, pulsed current gas tungsten witnessed superior corrosion-resistant behaviour. This phenomenon is observed due to grain refinement suppression of heat-affected zones and secondary phases in the weld fusion zone. In addition, the appearance of protective oxides such as Cr2 O3, NbO and NiCr2 O4 helps arrest the oxidation at the surface and sub-surface layer by providing good resistance against hot corrosion to the welded substrate. Thus, utilizing the PCGTAW technique during the fabrication/refurbishing process helps promote the material's corrosion resistance against a hot corrosion environment.